Causes of farmers’ aversion to organic vegetable production in Shyamnagar and Kaligonj Upazilla of Bangladesh - Alim, Md Samiul; Sultana, Mst Sharmin (International Journal of Agricultural Research, Innovation and Technology, 2023)
Agriculture is an ongoing changing field where farmers constantly change production technology by adopting different updated modern practices. The study explores the motivating factors influencing farmers to switch to synthetic pesticides dependent on farming from organic farming methods. The main factors are the lower price of organic vegetables, pesticide availability, social responsibility and economic considerations. The most challenging AEZ -13 coastal Satkhira has been taken for this study. The result shows that farmers who choose to switch give high importance to the production cost, price of organic vegetables, supply of bio-product, and availability of organic products than the moral, economic and social concerns. Int. J. Agril. Res. Innov. Tech. 13(1): 25-30, June 2023